Two lymphoma histotypes and papillary thyroid carcinoma coexisting on Hashimoto ground: a case report and review of the literature - Igor Iskra; Maja Ilić Tomaš; Tatjana Bogović Crnčić; Edvin Kukić; Ita Hadžisejdić; Manuela Avirović; Neva Girotto (BMC, 2024)
Abstract Background Papillary carcinoma is the most frequent type of thyroid carcinoma, while primary thyroid lymphoma is uncommon disease. The coexistence of these entities has already been described, and the common risk factor is considered Hashimoto thyroiditis. The two most frequent histotypes of primary thyroid lymphoma are diffuse large B-cell and mucosa-associated lymphoid tissue lymphoma, but the coexistence of both with papillary carcinoma is rarely reported. Methods We present a case of a previously healthy 57-years old male with rapidly growing lump on the right side of the neck. Ultrasonography revealed nodules in both thyroid lobes. Fine needle aspiration cytology and pertechnetate scintigraphy were performed. Due to the Bethesda T-5 in the "cold" nodule of the right lobe, surgery with histopathological and immunohistochemistry analysis was indicated. Results Histopathological and immunohistochemistry methods confirmed concomitant malignancies in the thyroid gland: diffuse large B-cell lymphoma and papillary carcinoma in the right, and mucosa-associated lymphoid tissue lymphoma in the left lobe with Hashimoto thyroiditis in the remaining tissue. Patient underwent therapy procedures and was without signs of local recurrence or metastatic spread on subsequent follow-up. Conclusions Sudden appearance of the neck mass in patients with Hashimoto thyroiditis should raise suspicion on primary thyroid lymphoma and be promptly taken in the diagnostic workup, including fine needle aspiration cytology. Pathology with immunohistochemistry is crucial for further clinical decision making. Since the standardized protocol in management of these complex patients is missing, personal approach and close collaboration between cytologist, pathologist, surgeon, haematologist and nuclear medicine specialist is essential.